Business Mentoring and Small-Scale Business Survival in Delta State - Iyamu, Ewemade (International Business Education Journal, 2021)
Small businesses commonly encounter difficulties in gaining access to credit facilities and continuous capacity building, which affected their survival. Therefore, this study aims to describe managers’ perspectives of business mentoring on small-scale business survival. Specifically, the study identifies the extent to which mentoring aid credit facility accessibility and promote capacity building for small scale business survival. The study utilized a descriptive survey research design. The study population was 1397 registered small scale enterprise in Delta Central Senatorial District of Delta State. A proportionate sampling technique was used to select 140 respondents for the study. Data was collected using a questionnaire as an instrument. Three experts validated the instrument, and Cronbach’s alpha statistics tested the reliability and yielded 0.97. Descriptive statistics of mean was used to answer the research questions with a mean average of 2.50 above as high extent and 2.49 below as low extent. The analysis results showed that mentoring promoted credit facility accessibility and supported the capacity building of entrepreneurs to a high extent to a high extent. Accordingly, it was recommended that there be a forum in states that would help identify mentors in all business sectors to guide credit facility accessibility. Furthermore, there is a need for a sound policy in which business mentoring should be anchored. The sound policy will guide capacity building and other sundry aspects of mentoring to mentees for improving business performance.